ARC6-mediated Z ring-like structure formation of prokaryote-descended chloroplast FtsZ in Escherichia coli - Hiroki Irieda (Nature Portfolio, 2017)
Abstract Plant chloroplasts proliferate through binary fission, and the stromal-side molecules that are involved in chloroplast division are bacterial derivatives. As in bacteria, the prokaryotic tubulin homolog FtsZ assembles into a ring-like structure (Z ring) at mid-chloroplast, and this process is followed by constriction. However, the properties of chloroplast FtsZs remain unclarified. Here, we employed Escherichia coli as a novel heterologous system for expressing chloroplast FtsZs and their regulatory components. Fluorescently labelled Arabidopsis FtsZ2 efficiently assembled into long filaments in E. coli cells, and artificial membrane tethering conferred FtsZ2 filaments with the ability to form Z ring-like structures resembling the bacterial Z ring. A negative regulator of chloroplast FtsZ assembly, ARC3, retained its inhibitory effects on FtsZ2 filamentation and Z ring-like structure formation in E. coli cells. Thus, we provide a novel heterologous system by using bacterial cells to study the regulation of the chloroplast divisome. Furthermore, we demonstrated that the FtsZ2-interacting protein ARC6, which is a potential candidate for Z ring tethering to the chloroplast inner envelope membrane, genuinely targeted FtsZ2 to the membrane components and supported its morphological shift from linear filaments to Z ring-like structures in a manner dependent on the C-terminal ARC6-interacting domain of FtsZ2.